The strange death of Europe: immigration, identity, Islam - Murray, Douglas (Bloomsbury, 2017)
Cover -- Contents -- Introduction -- 1 The beginning -- 2 How we got hooked on immigration -- 3 The excuses we told ourselves -- 4 'Welcome to Europe' -- 5 'We have seen everything' -- 6 Multiculturalism -- 7 They are here -- 8 Prophets without honour -- 9 Early-warning sirens -- 10 The tyranny of guilt -- 11 The pretence of repatriation -- 12 Learning to live with it -- 13 Tiredness -- 14 We're stuck with this -- 15 Controlling the backlash -- 16 The feeling that the story has run out -- 17 The end -- 18 What might have been -- 19 What will be -- Afterword -- Notes -- Acknowledgements -- Index.